1996
DOI: 10.1159/000217208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemorrhagic Effect of Heparin and Human Activated Protein C with Use of Thrombostat 4000

Abstract: The importance of bleeding as a complication of anticoagulant therapy is clearly recognized. We previously reported that amelioration of hemorrhage associated with disseminated in-travascular coagulation by the human activated protein C (APC) was greater than that by heparin. In this study, we compared the bleeding complication of intravenously administered APC and heparin in rabbits, and also estimated primary hemostasis. When both anticoagulants were intravenously infused, the bleeding time from a punctured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…This agrees with other experimental studies in rats, other animals, and humans [16,18,[26][27][28] . In this experiment, there was no signifi cant alteration of BT in the enoxaparin groups compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with other experimental studies in rats, other animals, and humans [16,18,[26][27][28] . In this experiment, there was no signifi cant alteration of BT in the enoxaparin groups compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…APC mediates the coagulation inhibition without the requirement of the host thrombin–thrombomodulin system. Such a benefit of APC is already represented by its efficacy in treating animal models of thrombus formation ( Gruber & Griffin, 1992) or DIC ( Katsuura et al , 1994 , 1996) . In this study, we showed that infused APC controlled the hypercoagulation in a protein C null individual ( Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…[47] In in vivo animal studies, little or no prolongation of bleeding time was detected in association with activated protein C administration. [43,46,47,50,51] Effects on Coagulation Markers in Patients with Sepsis Change over time and percentage change from baseline in plasma D-dimer levels (normal range 0.0 to 0.39 mg/L) were measured in patients who participated in the two randomised, double-blind, placebo-controlled trials of drotrecogin alfa (activated) [section 3]. [20,22] D-dimer levels indicate coagulation has occurred in conjunction with fibrinolysis activation, forming fibrin breakdown products.…”
Section: Mechanism Of Actionmentioning
confidence: 99%